Peran Surat Berharga Dalam Pengembangan Pasar Keuangan Dan Persiapan Investasi - Rizky Zainul Alam; Noraini Noraini; Sumriyah Sumriyah (Jurnal Relasi Publik, 2023)
This research is motivated by the effect of securities on financial market development and investment preparation. Securities have a role to determine how to develop financial markets. Talking about securities cannot be separated from trade transactions, because the birth of securities is intended to improve, facilitate and secure transactions in the world of commerce. Based on these problems, the authors conducted research on how securities can be used in developing financial markets and preparing for investment. This research method through the collection of case studies and data from previous journals. The conclusion of this study is that the existence of securities can regulate and control financial markets through existing laws.